Evaluating the effects of curcumin nano-chitosan on miR-221 and miR-222 expression and Wnt/β-catenin pathways in MCF-7, MDA-MB-231 and SKBR3 cell lines - Touba Eslaminejad; Seyed Noureddin Nematollahi-Mahani; Marzieh Lotfian Sargazi; Mehdi Ansari; Vida Mirzaie (BMC, 2024)
Abstract Background Breast cancer is one of the most common diseases worldwide that affects women of reproductive age. miR-221 and miR-222 are two highly homogeneous microRNAs that play pivotal roles in many cellular processes and regulate the Wnt/β-catenin signaling pathway. Curcumin (CUR), a yellow polyphenolic compound, targets numerous signaling pathways relevant to cancer therapy. The main aim of this study was to compare the ability of chitosan curcumin nanoparticle (CC-CUR) formulation with the curcumin in modulating miR-221 and miR-222 expression through Wnt/β-catenin signaling pathway in MCF-7, MDA-MB-231 and SK-BR-3 breast cancer cell lines. Method Chitosan-cyclodextrin-tripolyphosphate containing curcumin nanoparticles (CC-CUR) were prepared. Cytotoxicity of the CUR and CC-CUR was evaluated. Experimental groups including CC-CUR, CUR and negative control were designed. The expression of miR-221 and miR-222 and Wnt/β-catenin pathway genes was measured. Results The level of miR-221 and miR-222 and β-catenin genes decreased in MCF-7 and MDA-MB-231 cells and WIF1 gene increased in all cells in CC-CUR group. However, the results in SK-BR-3 cell line were unexpected; since miRs and WIF1 gene expressions were increased following CC-CUR administration and β-catenin decreased by administration of CUR. Conclusion Although the composite form of curcumin decreased the expression of miR-221 and miR-222 in MCF-7 and MDA cells, with significant decreasing of β-catenin and increasing of WIF1 gene in almost all three cell lines, we can conclude than this formulation exerts its effect mainly through the Wnt/β-catenin pathway. These preliminary findings may pave the way for the use of curcumin nanoparticles in the treatment of some known cancers.